User friendly IOT solution for multiple industries by adopting USB-enabled sensor/actuator modules and preconfigured computer - Chia, Shun Cheng (2020)
This project is an Internet of Things (IoT) device development project. The proposed solution will enable non-technical users to explore and customise an IoT solution with the least amount of technical knowledge and skill. Nowadays, the Internet of Things technology has become one of the key components that help a company to grow. However, customisation issue has become one of the biggest challenges faced by existing IoT applications. Due to lack of IoT platforms with capabilities to support multiple industries, companies are facing difficulties to develop custom IoT solutions based on their requirements. Besides, most of the existing IoT applications are lack of user-friendly characteristics. Implementation and modification of an IoT solution still required a technician. The proposed solution is to implement plug-and-play features for sensors and actuators by using microcontrollers and Universal Serial Bus (USB) technology. The main purposes of this project are to develop a user-friendly customisable IoT platform with plug-and-play sensors and actuators and to develop USB-enabled sensor/actuator modules by using customised microcontrollers. To realise the proposed solution, master-slave architecture is adopted by using a Raspberry Pi computer as master control board and Digispark ATTINY85 Mini USB Development Boards as slave devices. Raspberry Pi 3 model B+ is chosen to be the brain of the proposed solution due to its ability to handle high-level programs and the availability of Internet connectivity requirements. Besides, Digispark ATTINY85 Mini USB Development Board is suitable to act as a slave device due to its costeffectiveness and the abilities to integrate with sensors and actuators. Furthermore, Raspberry Pi 3 model B+ computer and Digispark ATTINY85 Mini USB Development Board are also capable to perform data transfer by using USB protocol in order to transmit sensor readings and allow commands to be passed. At the end of the project, a customisable IoT device and USB-enabled sensor/actuator modules will be developed to reduce the learning gap for a user to get familiar with the Internet of Things and enable fast setup for an IoT solution as well as providing ease of modification of an IoT solution.